Physicochemical characterization of four commercial rice varieties in Ghana - Diako, C.; Manful, J.T.; Johnson, P.N.T.; Sakyi-Dawson, E.; Bediako-Amoa, B.; Saalia, F.K. (Advance Journal of Food Science and Technology, 2011)
This study evaluated the physical characteristics, proximate and mineral composition, and functional properties of four commercial Ghanaian rice varieties compared to two imported rice brands to provide data for quality improvement. Imported brands were significantly different (p<0.05) from local varieties in grain dimensions and colour. Local varieties had higher mean values for grain width (2.21-2.26 mm), 1000-grain weight (19.5-22.3 g) and bulk densities (0.87-0.91 g/mL). Physical properties that negatively affect grain quality - brokens (13.60-32.70%); moldiness (0.89-22.3%); chalkiness (0.17-0.44%); and immature grains (0.05-0.33%) - were also higher. However, the local varieties were nutritionally superior to the imported brands, having higher iron (5.0-8.2 mg/kg) and phosphorous (1166-1374 mg/kg) contents. All the samples were nonwaxy rice types with high gelatinization temperatures (83.8-88.2°C), soft gels (66-98 mm) with low to intermediate amylose content (15.9-22.7%). The competitiveness of locally grown rice can be enhanced by improving physical quality and adopting a marketing strategy that emphasizes the nutritional quality and suitability for specific foods. © Maxwell Scientific Organization, 2011.
Keywords: Imported; Local; Marketing; Nutritional; Quality